The importance of usability in development of digital libraries - Vrana, Radovan (Array, 2007)
Digital libraries are among the most interesting electronic information resources of our time. They are the collection of services and the collection of information objects and services that support users in accessing information objects available on the Internet. They are complex information systems consisting of many components which depend on each other in their operation. To achieve the flawless operation of digital libraries their developers should evaluate their achievements during the phase of development as well as during the phase of use. As a result of their efforts, users should get usable and easy to use information systems which are adapted to their needs and preferences. Evaluation and usability are two important concepts which may help librarians and computer specialists to design better information systems and better services for them. Usability testing may include one (usually the user interface) or many components of an information system for evaluation. Evaluation also includes the research of user community. Information acquired in such a way may also significantly help in information system improvement. Since the goal of evaluation is to achieve quality and improvement, the final result should be a superior information system like digital library and satisfied users.